DEVELOPMENT OF A PERCEPTION SUBJECTIVIZATION COMPONENT FOR DIGITAL TWIN MODELS OF HUMAN-MACHINE INTERACTION SUBJECTS - PUKACH, ANDRII; TESLYUK, VASYL (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This research is devoted for resolution of scientific and applied problem of consideration (taking into account) the perception subjectivization of the object of human-machine interaction – by the subjects of this interaction, in digital twin models of human-machine interaction subjects. In order to solve the declared scientific and applied problem, a specialized perception subjectivization component has been developed for digital twin models of human-machine interaction subjects, which makes it possible to increase the potential and obtain further development of these models by expanding their conceptual purpose and functional capabilities, exploring the processes of not only human-machine interaction itself, but also, in addition, the issues of the subjective perception of human-machine interaction objects by the subjects of this interaction. In turn, the development and implementation of this component provides new opportunities in researching and solving relevant issues of the global scientific and applied problems of automation and intellectualization of human-machine interaction processes, as well as comprehensive support processes of software products, which is one of the relevant components of this interaction. A conceptual model of the declared component has been developed, which fully reflects the key principles of its structure and integrative properties and mechanisms. A basic mathematical model of the perception subjectivization component for digital twin models of human-machine interaction subjects has been developed, as well as a corresponding specialized algorithm for synthesizing this component within various and potential existing human-machine interaction models. Approbation of the developed component has been carried out on the example of solving the relevant practical task of identifying the most compatible subjects among the number of existing ones within the framework of the researched human-machine interaction. An analysis of potential research directions was conducted regarding the possibilities of further development(s) and improvement(s) of both the proposed component and human-machine interaction models as a whole, in the context of research area(s) of the scientific and applied problems of automation and intellectualization of the human-machine interaction processes, including software products’ comprehensive support as one of the relevant components of this interaction.
Keywords: human-machine interaction; perception subjectivization; model; automation; intellectualization